Effect of calcium salts and rennilase on white soft cheese - Chang, Suklin C
The acceptability of Rennilase and the effects of calcium carbonate and calcium sulfate on white cheese was determined in the study. In the first phase, Rennilase strength for use in native cheese-making was determined. It was found that 0.42 ml of diluted Rennilase (1ml Rennilase:40 ml water) was needed to clot 100 ml milk in 20 minutes. The effects of the two calcium salts on the yield and sensory properties of white cheese was determined on Phase II. Both salts added at 0.011M or 0.0125M concentration were found to give a lower yield than the control or untreated cheese and did not affect the sensory properties of the cheese. The control was found to contain 21.1% fat and 13.0% protein. In the third phase, the shelf-life of white cheese packages in three materials namely: banana leaves, polyethylene bags and polyethylene rigid containers, was determined. Acidity, loss in weight of curds and microbial load of all samples were found to increase upon storage. The ones stored in polyethylene rigid containers obtained higher scores in terms of general acceptability and had the longest shelf-life of about 9 days.